Ternary Organic Solar Cells with Reduced Graphene Oxide–Sb2S3 Hybrid Nanosheets as the Cascade Material. Issue 5 (12th June 2015) - Balis, Nikolaos; Konios, Dimitrios; Stratakis, Emmanuel; Kymakis, Emmanuel
Abstract: We demonstrate that the efficiency of a poly[N‐9′‐heptadecanyl‐2, 7‐carbazole‐alt‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole)](PCDTBT):[6, 6]‐phenyl‐C71 ‐butyric‐acid‐methyl‐ester (PC71 BM) bulk heterojunction solar cell can be improved from 5.53 % to 6.81 % by incorporating reduced graphene oxide–antimony sulfide (rGO–Sb2 S3 ) hybrid nanosheets as the third component. By using this hybrid as the cascade material, we combine the ultra‐conductive multi charge transfer paths provided by graphene with the favorable arrangement of the material energy bands due to the presence of Sb2 S3 nanocrystals. The higher lowest unoccupied molecular orbital (LUMO) energy level of rGO–Sb2 S3 relative to PC71 BM results in an increase of the open circuit voltage upon increasing the rGO–Sb2 S3 concentration, while the photocurrent and fill factor are enhanced due to the presence of more exciton dissociation interfaces and more efficient charge transport. Abstract : Hybrid composites : The synthesis and utilization of reduced graphene oxide–antimony sulfide (rGO–Sb2 S3 ) hybrid nanosheets as the cascade material in ternary organic solar cells is demonstrated. Its utilization in PCDTBT:PC71 BM blend leads to a power conversion efficiency of 6.81 %, a value 23 % higher than the efficiency of the binary devices without rGO–Sb2 S3.